Monitoring equity in universal health coverage with essential services for neglected tropical diseases: an analysis of data reported for five diseases in 123 countries over 9 years. Issue 9 (September 2018) - Fitzpatrick, Christopher; Bangert, Mathieu; Mbabazi, Pamela Sabina; Mikhailov, Alexei; Zouré, Honorat; Polo Rebollo, Maria; Robalo Correia e Silva, Magda; Biswas, Gautam
Summary: Background: A service coverage index has recently been proposed to monitor progress towards universal health coverage (UHC), and baseline results for 2015 are available. However, evidence on equity in that progress is scarce. The service coverage index did not consider services for neglected tropical diseases (NTDs), a group of preventable diseases defined by WHO member states on the basis of the disproportionate burden they place on their poorest, remotest, and otherwise most marginalised communities. Because of the much-needed equity lens that it could provide, NTD service coverage should not be neglected in efforts to monitor UHC progress. Methods: We developed an index focused on coverage of services for NTDs, comparable in methods to the UHC service coverage index. On the basis of data availability, we focused on preventive chemotherapy, which was recently included in the highest-priority package of essential UHC interventions. We used data reported to WHO since 2008 for the five NTDs amenable to preventive chemotherapy (lymphatic filariasis, onchocerciasis, schistosomiasis, soil-transmitted helminthiases, and trachoma) to develop an NTD service coverage index based on the geometric mean of coverage rates for individual NTD services with regularly reported data. We then compared this NTD service coverage index with the UHC service coverage index. A high UHC index value and a low NTD index value suggest that a country might not be adequately prioritising interventions for the poor. We measured Spearman rank-order correlation (ρ) of the NTD service coverage index with income inequality, as measured by the Gini coefficient (range of 0–1), where values of the Gini coefficient close to 1 indicate higher income inequality, and a negative correlation was evidence of socioeconomic barriers to health service coverage for people who are least well off. Findings: At least 123 countries can monitor NTD service coverage by use of a simple index. The median national NTD index was 32 in 2016, an increase from 3 in 2012, and from 0 in 2008. In 2015, the NTD index was lower than the UHC index in 81 of the 113 countries for which both NTD and UHC indices are available, by up to 80 points. The NTD index was negatively but weakly correlated with income inequality; this correlation was strongest in the African Region (ρ=–0·46 in 2008, ρ=–0·32 in 2015), suggesting that high-income inequality, although associated with low coverage of services targeting the poor, does not preclude the extension of that coverage. Interpretation: The NTD index can be used to measure equity in progress towards UHC. A broader NTD index including services for other NTDs could be developed at regional and country levels. Comparing the NTD and UHC service coverage indices reveals that some countries that are performing well by the measure of the UHC service coverage index still have work to do in prioritising services for their poorest and otherwise most marginalised communities. Our results offer hope that socioeconomic barriers to health service coverage can be overcome. Funding: None.